Developing a Research Mentorship Program: The American Society of Pediatric Nephrology's Experience - Vasylyeva, Tetyana L.; Díaz-González de Ferris, María E.; Hains, David S.; Ho, Jacqueline; Harshman, Lyndsay A.; Reidy, Kimberly J.; Brady, Tammy M.; Okamura, Daryl M.; Samsonov, Dmitry V.; Wenderfer, Scott E.; Hartung, Erum A. (Frontiers in Pediatrics, 2019)
Background: Mentor-mentee relationships provide support and guidance for the development of an academic physician’s research career. The experience in mentorship program implementation is valuable for medical fields in providing research opportunities to young faculty. Methods: The American Society of Pediatric Nephrology (ASPN) established a research mentorship program to a) assist with matching of appropriate mentor-mentee pairs and b) establish metrics for desirable mentor-mentee outcomes with two independent components: 1) the grants review workshop, a short-term program providing mentor feedback on grant proposals, and 2) the longitudinal program, establishing long-term mentor-mentee relationships. Regular surveys of both mentors and mentees were reviewed to evaluate and refine the program. Results: Twelve mentees and 17 mentors participated in the grant review workshop and 19 mentees were matched to mentors in the longitudinal program. A review of NIH RePORTER data indicated that since 2014, 13 NIH grants have been awarded. Mentees in the longitudinal program reported that the program helped most with identifying an outside mentor, improving grant research content, and with general career development. Mentors perceived themselves to be most helpful in assisting with overall career plans. Email communications were preferred over phone or face-to-face communications. Mentees endorsed strong interest in staying in touch with their mentors and 100% of mentors expressed their willingness to serve in the future. Conclusion: This mentorship program was initiated and supported by a relatively small medical society and has shown early success in cultivating mentoring relationships for a future generation of clinician-scientists and could serve as a model.